Analisis Efektivitas Tata Kelola Administrasi Kepegawaian di Balai Besar Guru Penggerak (BBGP) untuk Meningkatkan Efisiensi Layanan Pendidikan - Aulia, Siti; Stevanus, Kelvin; Mustofa, Yusup; Purnamasari, Ita; Agatha, Jesika (Jurnal Digital Bisnis, Modal Manusia, Marketing, Entrepreneurship, Finance, & Strategi Bisnis (DImmensi), 2025)
This study aims to analyze the implementation of human resource administration governance at the Balai Besar Guru Penggerak (BBGP), focusing on the Division of Governance and Human Resources, and its impact on the efficiency of educational services. A descriptive qualitative approach was used, with data collection techniques including observation, interviews, and documentation. The findings indicate that while the human resource administration system has been functioning well, several significant challenges remain, such as insufficient data digitalization, time efficiency issues, and suboptimal coordination between divisions. Based on the findings, it is recommended that BBGP strengthen the use of information technology in administrative systems, enhance employee competencies through training, and review and improve existing standard operating procedures (SOPs) to support better governance efficiency and educational service delivery.